Some forms of Bushmen art - Walton, James (International Library of African Music, 1957)
The majority of the rock paintings in Southern Africa belong to the last six hundred years although crude monochromes were being painted much earlier. The engravings, which include extinct animals, are, in part at least, older than the paintings but they also have continued down to recent times. It has frequently been asserted that the Bushmen could not have been the artists responsible for the rock paintings and engravings because today they do not practise any similar artistic expression. But, apart from those paintings which are undoubtedly attributed to Bushmen during the last hundred and fifty years, there are other forms of Bushman art which are closely related to the rock engravings and paintings and which shed considerable light on their origin.
Keywords: African Music